Potpourri of interesting scalp lesions - Hegde, Shreya; Samartha, Vinitha (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Painless soft tissue masses on the scalp are commonly encountered in clinical practice. The most likely diagnoses still remain as epidermoid cysts, sebaceous cysts and benign lipomas. The aim of this study is to exhibit the vast variety of scalp lesions, with emphasis on the metastatic scalp lesions. Materials and Methods: This was a retrospective study carried out in the Department of Pathology in a tertiary care hospital in coastal Karnataka, India. A total of 29 scalp lesions received during the period were included in the study. Paraffin blocks and slides along with case records were retrieved and studied. Results: Out of a total of 29 scalp lesions included in this study, the most common lesion was lipoma. The most interesting cases were the 5 cases of scalp lesions which were metastasis from visceral organs, the most common site being the thyroid. Conclusion: A wide histopathological range of lesions comprising of neoplasticand non-neoplastic lesions were found. The most common lesion in this study was lipoma, while the most interesting were metastatic scalp lesions.